MENCIPTAKAN SISTEM PERADILAN EFISIEN DENGAN SISTEM E-COURT PADA PENGADILAN NEGERI DAN PENGADILAN AGAMA SE-TANGERANG RAYA - Susanto Susanto; Muhamad Iqbal; Wawan Supriyatna (STIH Putri Maharaja, 2020)
Based on the Decree of the Secretary of the Supreme Court of the Republic of Indonesia Number: 305/SEK/SK/VII/2018, the Supreme Court has chosen 17 District Courts, 6 State Administrative Courts and 9 Religious Courts as the Pilot Project Court for the e-court Application. On this basis, the sample of the court taken by the author is the District Court and Religious Court which is located in Tangerang Raya. The author will focus on the effectiveness and efficiency with regard to the role of the e-court system in the administrative system of the district and religious courts in Tangerang Raya. The large amount of time and files involved are considered far from the principles of fast, simple and low cost trial. It is hoped that time and cost efficiency problems can be resolved with E-court. To prove the test of the effective role of e-court in realizing fast, simple and low cost judiciary from the segmentation of district and religious courts in Tangerang Raya, the E-court system in state and religious courts in the Greater Tangerang area in segmentation creates efficiency in the case administration service process.